2008
DOI: 10.1080/07474930802388009
|View full text |Cite
|
Sign up to set email alerts
|

Pairwise Likelihood Inference for General State Space Models

Abstract: This article concerns parameter estimation for general state space models, following a frequentist likelihood-based approach. Since exact methods for computing and maximizing the likelihood function are usually not feasible, approximate solutions, based on Monte Carlo or numerical methods, have to be considered. Here, we concentrate on a different approach based on a simple pseudolikelihood, called “pairwise likelihood.” Its merit is to reduce the computational burden so that it is possible to fit highly struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 28 publications
0
48
0
Order By: Relevance
“…However, previous studies (Varin and Vidoni, 2009, Varin and Czado, 2010 have shown that spatial dependency drops quickly with interobservation distance. Therefore, there is no need to retain all observation pairs because the pairs formed from the closest crashes provide much more information than pairs from crashes that occur far from one another.…”
Section: Model Estimationmentioning
confidence: 87%
“…However, previous studies (Varin and Vidoni, 2009, Varin and Czado, 2010 have shown that spatial dependency drops quickly with interobservation distance. Therefore, there is no need to retain all observation pairs because the pairs formed from the closest crashes provide much more information than pairs from crashes that occur far from one another.…”
Section: Model Estimationmentioning
confidence: 87%
“…For instance Heagerty and Lele (1998) recommended to consider only significant lags but only to save computations. Varin and Vidoni (2007) There exist other ways to construct CL in a space-time setting. For instance the approximating likelihoods on selected blocks introduced by Caragea and Smith (2005) are special cases of the CL.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Almost all earlier research efforts employing the CML technique have used the pairwise approach in which the observed events e A correspond to a pair of observations from the (QT×1) vector m. These earlier studies include Apanasovich et al, (2008), Varin and Vidoni (2009), Engle et al (2007), Bhat et al (2010a), and Bhat and Sener (2009). Alternatively, the analyst can also consider larger subsets of observations, such as triplets or quadruplets or even higher dimensional subsets (see Engler et al, 2006 andCaragea and.…”
Section: The Composite Marginal Likelihood Approachmentioning
confidence: 99%
“…Procedures similar to those available with the maximum likelihood approach are also available for model selection with the CML approach (see Varin and Vidoni, 2009, Pace et al, 2011and Bhat, 2011. The statistical test for a single parameter may be pursued using the usual t-statistic.…”
Section: Model Selectionmentioning
confidence: 99%